Investigation on dynamic response and compaction degree characterization of multi-layer asphalt pavement under vibration rolling - Hongyu Shan; Han-Cheng Dan; Shiping Wang; Zhi Zhang; Renkun Zhang (Electronic Research Archive, 2023)
Asphalt mixture is composed of asphalt binder with aggregates of different sizes and compacted under static or dynamic forces. In practical engineering, compaction is a critical step in asphalt pavement construction to determine the quality and service life of pavement. Since the dynamic response characteristics of asphalt pavement can reflect the compaction state of asphalt mixture in the process of compaction, the establishment of the relationship between dynamic response characteristics and compaction degree is definitely significant. In this paper, a series of vibration sensors were adopted to capture the dynamic response signal of the vibration drum and asphalt mixture in the process of vibrating compaction for different surface courses of pavement. Then, the change regulations of vibration acceleration of vibrating drum and asphalt mixture were analyzed, and the quantitative linear relationship was established between accelerations of vibrating drum and asphalt pavement compactness. Further, the concept of evaluation unit (i.e., within 2 meters along the driving direction of the roller) and prediction method of compaction degree were proposed as well. The results showed that under the same vibration compaction condition, the compaction degree values of the top, middle and bottom layers have obvious differences, which should be taken seriously into consideration in the compaction process. Meanwhile, there is little difference which respectively are 2.8, 1.3 and 0.82% for the top, middle and bottom layers between the compaction degrees obtained by the proposed method and measured test. Therefore, the average value of the acceleration peak value of vibration drum within the evaluation unit can be adopted as the characterization index of the compaction degree of asphalt pavement. The investigation of this study can provide the technical reference for compaction control of asphalt pavement to a large extent.